2016
DOI: 10.3389/fmicb.2016.01128
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Effluents Are One of Several Sources of Metal, Antibiotic Resistance Genes, and Bacterial Markers Disseminated in Sub-Saharan Urban Rivers

Abstract: Data concerning the occurrence of emerging biological contaminants such as antibiotic resistance genes (ARGs) and fecal indicator bacteria (FIB) in aquatic environments in Sub-Saharan African countries is limited. On the other hand, antibiotic resistance remains a worldwide problem which may pose serious potential risks to human and animal health. Consequently, there is a growing number of reports concerning the prevalence and dissemination of these contaminants into various environmental compartments. Sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(52 citation statements)
references
References 80 publications
2
49
0
1
Order By: Relevance
“…The values ranged from 92.6-242.7, 76.5-163.2, 67.4-89.8 mg kg -1 for the sites R1, R2, and R3, respectively. The results obtained are in agreement with our previous studies, which demonstrated that there are large variations in the distribution of TC, TN, TP and grain size in sediments from some urban rivers located in the city of Kinshasa (Mubedi et al, 2013;Tshibanda et al, 2014;Kilunga et al, 2016;Laffite et al, 2016).…”
Section: Physicochemical Characteristics Of Sedimentssupporting
confidence: 92%
See 2 more Smart Citations
“…The values ranged from 92.6-242.7, 76.5-163.2, 67.4-89.8 mg kg -1 for the sites R1, R2, and R3, respectively. The results obtained are in agreement with our previous studies, which demonstrated that there are large variations in the distribution of TC, TN, TP and grain size in sediments from some urban rivers located in the city of Kinshasa (Mubedi et al, 2013;Tshibanda et al, 2014;Kilunga et al, 2016;Laffite et al, 2016).…”
Section: Physicochemical Characteristics Of Sedimentssupporting
confidence: 92%
“…The discharge of untreated urban effluents into river environments is a major concern in developing countries. Given this fact, in recent years accumulation of heavy metals in river sediments from developing countries have been reported with more attention (Mubedi et al, 2013;Devarajan et al, 2015b;Tamim et al, 2016;Laffite et al, 2016). Hydrophobic organic compounds (HOCs), such as PAHs, PCBs, and OCPs have been identified as environmental pollutants in all environmental compartments (Wu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of bla CTX-M containing strains from samples taken in November 2014, December 2014 and January 2015 together with amplification in standard PCR demonstrated that microbes harboring this gene were present at Awba at several time points. The absolute and relative abundances of bla CTX-M-1 measured at the site were similar to that reported for the sediment of Lake Brêt, Switzerland [81], an urban river in Kinshasa, Democratic Republic of Congo [82], and in waste water treatments plants and urban wetlands in the United States [83], but slightly lower than that measured in a river receiving hospital effluents in Tamil Nadu, India [84]. In all of those studies primers targeting Group 1 bla CTX-M were used.…”
Section: Abundances Of Marker Genes In the Wetlandssupporting
confidence: 78%
“…Previous work has also suggested that the increased relative abundance of intI1 could enhance the potential for HGT of ARGs and has a strong positive correlation with the Zn content in activated sludge bioreactors (Peltier et al, 2010). In addition, heavy metal and antibiotic resistance are frequently linked on the same plasmid (Baker-Austin, Wright, Stepanauskas, & McArthur, 2006;Laffite et al, 2016), and increased mobilization under metal selective stress might increase the possibility of ARGs spreading to human pathogenic bacteria (Zhu et al, 2013).…”
Section: Impacts Of Zn Exposure On Relative Abundance Of Mges In Soilmentioning
confidence: 99%